2019
DOI: 10.5539/jps.v8n2p62
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydroponics Systems on Growth, Yield and Quality of Zucchini (Cucurbita pepo L.)

Abstract: There is dearth of information pertaining to hydroponics production of zucchini in the Kingdom of Eswatini. The objective of this study was to determine the effects of hydroponics systems on growth, yield and nutritional content of zucchini. The research was conducted in three greenhouses of the Horticulture Department, Faculty of Agriculture, Luyengo Campus at the University of Eswatini between July and October 2018. The experiment was laid out in a split-plot design replicated four times. Three hydroponics s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Squash has a very high nutritional content with a lower glycemic index. Though squash fruits are high in vitamins (vitamins B, C, and A), minerals (especially K+), flavonoids, and phenolic compounds, their glycemic index is very low, which encourages their consumption worldwide, particularly in Europe and the Mediterranean regions [ 8 , 9 ]. In addition to the numerous health benefits of squash fruit consumption, several studies have reported the potential antioxidant, anticancer, and antidiabetic applications of squash fruits and flowers [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Squash has a very high nutritional content with a lower glycemic index. Though squash fruits are high in vitamins (vitamins B, C, and A), minerals (especially K+), flavonoids, and phenolic compounds, their glycemic index is very low, which encourages their consumption worldwide, particularly in Europe and the Mediterranean regions [ 8 , 9 ]. In addition to the numerous health benefits of squash fruit consumption, several studies have reported the potential antioxidant, anticancer, and antidiabetic applications of squash fruits and flowers [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Squash plants ( Cucurbita pepo L.) are among the CMV’s plant hosts. The plant fruits are cultivated worldwide for human consumption, especially in the Mediterranean territories and Europe [ 10 , 11 ]. The plant fruits’ high nutritional value encourages their consumption due to their high content of several essential vitamins (vitamins A, C, and B), minerals such as K+, and phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%